TRANSFORMASI METODE DAKWAH: MENGINTEGRASIKAN VIRTUAL REALITY JOURNEY DALAM PENYAMPAIAN PESAN DAKWAH - Al Kahfi Al Kahfi (STAI DI AL-HIKMAH, 2025)
This study aims to analyze the transformation of da’wah methods through the integration of Virtual Reality (VR) journeys in enhancing religious understanding and spiritual experiences of the mad’u. The research addresses a gap in previous studies that mostly focus on conventional digital media such as social media and websites, without specifically exploring immersive technologies like VR. Employing a qualitative approach, this study is based on a synthesis of recent literature and in-depth interviews with digital da’wah practitioners, Islamic VR content creators, and users of religious-themed VR content. The findings reveal that VR holds a distinctive potential in delivering immersive, affective, and reflective religious experiences. Simulations of sacred spaces (e.g., Masjid al-Haram), Islamic historical events, and interactive narratives effectively evoke empathy, deepen the comprehension of Islamic values, and strengthen spiritual consciousness. Compared to conventional methods, VR offers a heightened sense of presence and emotional impact. This study contributes a novel perspective to the digital da’wah discourse by proposing VR journey integration as a transformative method aligned with the visual, interactive, and experiential nature of the digital generation.